Depression as an Independent Risk Factor for Mortality in Critically Ill Patients. Issue 2 (February 2015) - Wewalka, Marlene; Warszawska, Joanna; Strunz, Volker; Kitzberger, Reinhard; Holzinger, Ulrike; Fuhrmann, Valentin; Zauner, Christian; Miehsler, Wolfgang; Moser, Gabriele
ABSTRACT: Objective: Mortality on medical intensive care units (ICU) is approximately 25%. It is associated with age, severity of illness, and comorbidities. Preexisting depression is a risk factor for worse outcome in many diseases. The impact of depression on outcome of ICU patients has not been investigated. We assessed a possible association between mortality and preexisting depressive mood at the time of ICU admission. The primary end point was 28-day mortality. Methods: This single-center cohort study was conducted in a tertiary medical ICU. Two hundred patients were evaluated for preexisting depressive mood at ICU admission, determined by Hospital Anxiety and Depression Scale (HADS) score ≥8 in the depression dimension in patients with appropriate cognitive function. Patients with insufficient cognitive function were assessed using observer rating by next of kin by Hammond scale (cutoff ≥4) and/or a modified version of the Hospital Anxiety and Depression Scale for observer rating (cutoff ≥10). Results: In total, 66 (33%) of 200 patients were classified with preexisting depressive mood. Forty-nine (24.5%) of 200 patients had died by day 28. Of these, 23 (47%) had preexisting depressive mood as compared with 43 of 151 (29%) 28-day survivors ( p = .017). Multiple logistic regression analysis revealed that preexisting depressive mood at the time of ICU admission is an independent risk factor for 28-day (odds ratio = 2.2, 95% confidence interval = 1.08–4.5, p = .030) and in-hospital mortality (median time till death = 20.5 [2–186] days, odds ratio = 2.58, 95% confidence interval = 1.31–5.1, p = .006). Conclusion: Preexisting depressive mood might be an independent risk factor for 28-day mortality in medical ICU patients. This could have diagnostic and therapeutic implications for critically ill patients.